Lower Serum Calcium Level Is Associated With Hemorrhagic Transformation After Thrombolysis. Issue 5 (May 2015) - Guo, Yang; Yan, Shenqiang; Zhang, Sheng; Zhang, Xiaocheng; Chen, Qingmeng; Liu, Keqin; Liebeskind, David S.; Lou, Min
<x xml:space="preserve">Abstract</x> Background and Purpose— We aim to investigate whether lower admission serum calcium levels are associated with hemorrhagic transformation (HT) after intravenous thrombolysis (IVT). Methods— A total of 362 patients treated with IVT was divided into 4 quartiles based on admission serum calcium levels (Q1[<2.16], Q2[2.16, 2.23], Q3[2.24, 2.31], and Q4[>2.31] mmol/L). HT was classified as hemorrhagic infarction and parenchymal hemorrhage. Logistic regression was applied to assess the association between serum calcium levels and the incidence of HT. Results— Compared with Q4, HT was more common in Q1 (odds ratio, 2.580; 95% CI, [1.258–5.292]; P=0.010), Q2 (odds ratio, 2.382; 95% CI, [1.163–4.877]; P=0.018), and Q3 (odds ratio, 2.293; 95% CI, [1.133–4.637]; P=0.021). Hemorrhagic infarction was more common in Q1 (P=0.037), and Q2 (P=0.018), compared with Q4, and parenchymal hemorrhage was more common in Q1 (P=0.029) than Q4. Conclusions— Lower admission serum calcium level is independently associated with HT after IVT, and this hypothesis needs larger confirmatory trials.